1997
DOI: 10.1159/000268007
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Expression of Endothelial Antigen PAL-E Indicates Absence of Blood-Ocular Barriers in the Normal Eye

Abstract: The endothelium-specific antigen PAL-E is expressed in capillaries and veins throughout the body with the exception of the brain, where the antigen is absent from anatomical sites with a patent blood-brain barrier. In this study we determined vascular endothelial staining for PAL-E in the normal eye in relation to the ocular blood-tissue barriers. Immunohistochemical staining of frozen tissue sections of eyes from 22 cornea donors and a number of normal animal autopsy eyes was performed for the PAL-E antigen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 21 publications
(35 reference statements)
2
28
0
Order By: Relevance
“…We also found that loss of the blood-retina barrier in DR is associated with increased expression of the PAL-E antigen in retinal capillary endothelium [18]. This may be based on changes in the number and/or structure of the pinocytotic vesicles of endothelial cells, as at the ultrastructural level, the endothelium-specific PAL-E antigen is located in pinocytotic vesicles [19][20][21]. In other pathological conditions characterised by loss of the blood-brain barrier, such as primary and metastiatic brain tumours, PAL-E also appears in the endothelium of leaky vessels [19,22,23].…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…We also found that loss of the blood-retina barrier in DR is associated with increased expression of the PAL-E antigen in retinal capillary endothelium [18]. This may be based on changes in the number and/or structure of the pinocytotic vesicles of endothelial cells, as at the ultrastructural level, the endothelium-specific PAL-E antigen is located in pinocytotic vesicles [19][20][21]. In other pathological conditions characterised by loss of the blood-brain barrier, such as primary and metastiatic brain tumours, PAL-E also appears in the endothelium of leaky vessels [19,22,23].…”
Section: Introductionmentioning
confidence: 55%
“…It is expressed by fenestrated and most continuous endothelia of vessels with non-specific permeability for plasma proteins. Endothelium in sites with a blood-brain barrier, including retina and iris, lacks the antigen [20,21]. In pathological conditions with loss of the blood-brain barrier, like brain tumors, but also in DR, PAL-E appears in the leaky endothelium [18,19,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…The similarity in phenotype is shown by our immunohistochemical findings, as we found expression of two BBB markers which are both functionally involved in the blood-brain barrier, Glucose-transporter-1 and PGlycoprotein, and lack of expression of the PAL-E antigen in the iris and ciliary muscle capillaries. The endothelium specific PAL-E antigen is absent from normal BBB endothelium in the brain and eye (Schlingemann et al, 1988(Schlingemann et al, , 1997Leenstra et al, 1993) and is associated with pinocytotic vesicles which are scarce in BBB endothelium (Reese and Karnovsky, 1967 ;Schlingemann et al, 1985Schlingemann et al, , 1991. Functionally, our tracer study in the rabbit showed that ciliary muscle capillaries are impermeable for HRP.…”
Section: Discussionmentioning
confidence: 99%
“…In areas with a patent blood-tissue barrier the antigen is not found. The PAL-E antigen therefore appears to be a marker indicating sites with an absent blood-tissue barrier (Schlingemann et al, 1988(Schlingemann et al, , 1997.…”
Section: Introductionmentioning
confidence: 99%
“…Staining of serial sections with PAL-E was performed to identify capillaries and venules that are not involved in a blood-tissue barrier, whereas this antigen is absent in lymphatic endothelium. Anti-CD31 was used as a marker for all blood and lymph vessel endothelium (Schlingemann et al 1985(Schlingemann et al ,1997Ruiter et al 1989).…”
Section: Light Microscopic Immunohistochemistrymentioning
confidence: 99%